The uptake of educational technology in South African Higher Education: a study of the context that conditioned emergency remote teaching in the pandemic - Ngcobo, Nomathemba Faustinah (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
The study explores the enablements and constraints in the uptake of educational technologies in the South African higher education system. This is a multiple institutional study which considers the differentiated nature of higher education institutions in South Africa and reflects on the implications of this for the use of educational technology (EdTech). EdTech is seen as an important aspect of 21st century education. As an established practice in many universities it has made a significant impact on teaching and learning practices. However, EdTech is often presented as a panacea to educational problems and implemented without consideration of the contexts in which it is used. Data was collected from the educational technology units of 22 of the 26 public higher education institutions and the main sources of this data were an online survey questionnaire related to the uptake of educational technologies and semi-structured interviews. For the research analysis, Archer's analytical dualism and morphogenetic cycle provided a framework with the understanding that a social phenomenon such as EdTech emerges from a complex interplay of multiple mechanisms rather than through simple unidirectional causality. The framework directed me to analyse structure, culture and agency as separate entities allowing an understanding of the complex and rapidly growing phenomenon of EdTech. Analytical dualism provides guiding principles on how agential actions, structural resources, and cultural practices emerge and allows an understanding of how agents experience and respond to structures and cultures in social fields, for example, the uptake of EdTech for teaching and learning. The morphogenetic cycle reveals the historical nature the EdTech uptake with events happening over a period of time so that past events, which possess structural and cultural mechanisms, condition agency in socio-cultural interaction. The study identified several mechanisms enabling and constraining the uptake of EdTech, and while the findings are not exhaustive, they do indicate important enablements and constraints which the sector would do well to consider as it enters a post-pandemic phase. The data was collected prior to the pandemic and thus provides an understanding of what allowed for the uptake of EdTech when face-to-face teaching and learning was the norm. While the pandemic resulted in a rapid pivot to Emergency Remote Teaching (ERT), and fundamentally changed the face of EdTech in the South African higher education sector and around the world, the findings of this study remain pertinent. Archer argues that when a new person or structure is introduced, it occurs within a pre-existing context and so what emerges should not be seen to be simply caused by that new person or structure. Rather, its emergent properties are exercised within the conditioning effects of the pre-existing structures, cultures and agents. The Covid-19 virus brought about significant effects around the world, but it would be a mistake for us to assume that the effects were the same across different national higher education systems or even across different universities within a country. For us to understand both what occurred during the pivot to ERT and to consider the implications of this for the future of EdTech, it is imperative that we understand the pre-existing conditions in which ERT was implemented. This thesis offers a rich picture of these pre-existing conditions. Key findings include the extreme extent to which universities differed in their resourcing and uptake of EdTech prior to the pandemic. In some universities, there were well-resourced EdTech centres while in others, the implementation of EdTech was seen to be the responsibility of the IT department. Even where EdTech staff were employed, the nature of this employment varied greatly. In some cases, such staff were seen as educational experts who were hired as academics and often worked within academic development centres. In other cases, such staff were employed as administrative support staff. Another difference pertained to whether they were employed on contract (often funded through project funding) or on a permanent basis. These differences in employment and the positioning of the EdTech staff were seen to greatly condition the levels of credibility they enjoyed and the kinds of work they could undertake. If they were employed as support staff, they were more likely to be seen to be responsible for providing academics with end-user technical assistance. If they were employed as academics, they were more likely to be seen to be responsible for providing pedagogical and curriculum development support in using EdTech for teaching and learning. Another set of findings related to the extent to which EdTech was seen to be valued within each university, such as by being included in promotions criteria, mentioned in institutional strategies, and supported by university management. Where this was not the case, this constrained the uptake of EdTech. In all cases, the EdTech staff reported working almost exclusively with academics who sought to develop their EdTech capability on a voluntary basis because it aligned to what Archer terms their 'personal projects'. At times a departmental champion, especially in the form of the Head of Department as a social actor, led to EdTech uptake spreading across the academic body. There was evidence of some resistance to the use of EdTech and a great deal of anxiety among some academics. This was seen to be implicated in concerns that at times EdTech was seen to be a 'dumping ground' and the Learning Management System positioned simply as a repository of materials. Many academics reported being pushed by their students to integrate more technology in their teaching. Many students seem to be adept at using technology and can see its potential pedagogical benefits and so placed pressure for this to be increased. There were however concerns that the notion of 'Digital Natives', that is millennial students who were born into a technological era, was only a partial picture of the student body. The 'Digital Divide' meant that there was highly uneven access to hardware, data, bandwidth, and technological literacies among the student body. For many students, their only access to technology was while they were physically on campus, a finding that was to have extreme implications for the pivot to ERT. This research will be valuable to the field of educational technology and enhance the understanding of what is needed to enable the uptake of educational technologies in higher education teaching and learning in pedagogically sound ways. As the sector responds to the pandemic and reflects on lessons learned during this time, it will be important to look to the conditions outlined in this study as they continue to enable and constrain the uptake of educational technology.,Ucwaningo olwethulwe yindlela elandela imigomo ka-Bhaskar kanye no-Archer yesayensi yezenhlalo ehlola ukuze inikeze incazelo yokuvumeleka nezithiyo ekuthathweni kwezifundo ezisekwe ubuchwepheshe besimanje. Lolu ucwaningo lwezikhungo eziningi zemfundo ephakeme, futhi inhloso yalo enkulu bekuwukuhlonza ukuthi kwavela kanjani izindlela ezehlukene ukuze kuvunyelwe futhi kuvinjwe ukusetshenziswa kobuchwepheshe bezemfundo ezikhungweni zemfundo ephakeme ezehlukene eNingizimu Afrika. Izifundo ezisekwe ubuchwepheshe besimanje (EdTechs) ibonwa njengezici ezibalulekile zemfundo yekhulu lamashumi amabili nanye (21st century), futhi njengomkhuba osunguliwe emanyuvesi ibe nomthelela omkhulu ekufundiseni nasekufundeni. Kodwa-ke, i-EdTechs ivame ukwethulwa njengekhambi ezinkingeni zemfundo futhi yacwaningwa ngaphandle kokucabangela izimo lapho isetshenziswa khona. Ngenxa yalokho, kwaba nesidingo sokuqonda kangcono ukuthi ukutholwa kwayo kwehlukaniswa kanjani phakathi nohlelo lwemfundo ephakeme olungalingani emaNyuvesi ahlukene. Ubufakazi buqoqwe ezingxenyeni zobuchwepheshe bezemfundo zezikhungo zemfundo ephakeme zikahulumeni ezingamashumi amabili nambili (22) kwezingamashumi amabili nesithupha (26) futhi imithombo eyinhloko yalobufakazi kwakuwuhlu lwemibuzo lwenhlolovo oluku-inthanethi oluhlobene nokusetshenziswa kobuchwepheshe bezemfundo kwase kulandela kanye nezingxoxiswano ezihlelwe kancane. Ukuze kuhlaziywe ucwaningo, i-analytical dualism ngokuka-Archer kanye nomjikelezo we-morphogenetic (uzalo kabusha) unikeze uhlaka lokuhlaziywa kokutholwa kobuchwepheshe bezemfundo njengokusebenzelana okuqhubekayo phakathi kwezifundiswa nabasebenzi bomnyango bobuchwepheshe besimanje (EdTech staff). Ekuhlaziyeni, ngixoxa ngokuthi uhlaka lungiqondise kanjani ukuba ngihlaziye isakhiwo, isiko kanye nokwenza kwabantu njengezinhlangano ezihlukene nokuthi kungani lolu hlaka lufaneleka ukuze siqonde lesi simo esiyinkimbinkimbi nesikhula ngokushesha sezemfundo zobuchwepheshe besimanje. Ubumbaxambili bokuhlaziya buhlinzeka ngohlaka oluvumela abacwaningi ezimweni zomphakathi ukuthi babone futhi bahlaziye izindlela ezikhiqizayo neziyisisekelo, okuhlanganisa izindlela zokwenza ngokusebenzisa ukuxhumana komphakathi. Iphinde inikeze izimiso eziqondisayo zokuthi ezinye izenzo zokwenza komuntu kanye nemikhuba yamasiko zivela kanjani kanye nokuqonda ukuthi abenzi nabasebenzi bezemfundo, nokuthi abhekana kanjani futhi asabela kanjani ezakhiweni namasiko emikhakheni yezenhlalo, isibonelo, ukutholwa kwe-EdTechs ekufundiseni nokufunda. Ngaphezu kwalokho, umjikelezo we-morphogenetic wembula ubunjalo bomlando ukuthathwa kwe-EdTechs nezenzakalo ezenzeka esikhathini esithile ukuze izehlakalo ezidlule ezinezindlela zesakhiwo nezamasiko zibekezelele izenzo zezifundiswa njenge-ejensi ezovela ekusebenzelaneni kwezenhlalo namasiko. Izakhiwo ezivelayo zesakhiwo, isiko kanye nezabenzi zibonwa njengezindlela ezibalulekile ezivumela futhi zibambe iqhaza ekuthathweni kobuchwepheshe bezemfundo ekufundiseni nokufunda yizifundiswa. Ngakho-ke, ucwaningo luveza ukuthi kungani ukuthathwa kunezindlela ezivumelayo neziphoqayo futhi ukuxhumana phakathi kwesakhiwo, isiko kanye nomenzi kudala ukucabangela kwesimo okungaba okuncomayo noma okuphikisanayo ngokwemvelo. Imvume yokulandelana kwesimo yencazelo yokuthi kungani kunokuhlangenwe nakho okuhlukile ekuthathweni kwalawa ma-EdTech avela ezikhungweni ezehlukene esimweni semfundo ephakeme yaseNingizimu Afrika. Lolu cwaningo luzobaluleka emkhakheni wezobuchwepheshe bezemfundo futhi luthuthukise ukuqonda kwalokho okudingekayo ukuze kusetshenziswe ubuchwepheshe bezemfundo ekufundiseni nasekufundeni imfundo ephakeme.,Thesis (PhD) -- Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2022
Keywords: Educational technology -- South Africa; Education, Higher -- South Africa; Academic development; COVID-19 Pandemic, 2020- -- South Africa; Distance education Computer-assisted instruction; Web-based instruction -- South Africa